KONSEP AD‘ĀFAN: STUDI TAFSIR TEMATIK - Ruslansyah, Aldhy; Akmir; Nurfadhilah Syam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Based on the findings, it is discovered that the concept of multiplied sustenance in the Qur'an, associated with the word ad’āfan, is often understood solely in material terms. Some interpreters emphasize its spiritual meaning and blessings. This gap in understanding presents an opportunity for deeper research. The aim of this study is to identify and analyze the context of the Qur'anic verses that use the worod ad’āfan in relation to the concept of sustenance and to examine the interpretations of various scholars regarding the verses containing the word ad’āfan in relation to the reward of multiplied sustenance. This research employs a library research method, focusing on the word ad’āfan (أَضْعَافًا) found in several Qur'anic verses related to the concept of multiplied sustenance. The data collection technique involves reviewing the Qur'anic verses that contain the word ad’āfan, studying classical and contemporary interpretations and gathering supporting literature such as books, journals and relevant scholarly works. The results indicate that the word ad’āfan in the Qur'an carries the meaning of receiving double rewards granted by Allah to His servants according to their sincerity, piety and sacrifices in the path of goodness. Furthermore, this multiplication is not limited to material aspects but also includes spiritual dimensions, such as peace of mind, blessings in life and each other. The analyzed verses demonstrate that multiplied sustenance is granted to those who give charity with a sincere heart, without causing harm or bringing up their donations. For future research, it is hoped that the study of the concept of ad’āfan will utilize various approaches.